Pedagogical Scholarship in Public Health: A Call for Cultivating Learning Communities to Support Evidence-Based Education. (November 2017) - Merzel, Cheryl; Halkitis, Perry; Healton, Cheryl
Public health education is experiencing record growth and transformation. The current emphasis on learning outcomes necessitates attention to creating and evaluating the best curricula and learning methods for helping public health students develop public health competencies. Schools and programs of public health would benefit from active engagement in pedagogical research and additional platforms to support dissemination and implementation of educational research findings. We reviewed current avenues for sharing public health educational research, curricula, and best teaching practices; we identified useful models from other health professions; and we offered suggestions for how the field of public health education can develop communities of learning devoted to supporting pedagogy. Our goal was to help advance an agenda of innovative evidence-based public health education, enabling schools and programs of public health to evaluate and measure success in meeting the current and future needs of the public health profession.